Fostering Innovation and Methodology through Experiential Learning for Data Structures - Dr., Anitha Kumari; Dr., Nanda Gopal; Padmashani, Padmashani (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
For real-life work environment, developing employability skills by the students’ community is indispensable and need of the hour. Laboratories associated with courses cultivate the ability of students to think independently and promote employability skills through experiential learning. Data structures are one such predominant course in IT/CSE domain to enhance the skill set of students for Placements/Higher studies. It provides opportunity for students to devise algorithms efficiently in an optimal manner by solving challenging problems easily thereby gaining confidence for attending placements. The purpose of this paper is to foster innovation by exploration in data structures course through experiential learning by providing coding based challenging questions as tutorials, assignment presentations and as activities during laboratory sessions and online classes are to be conducted as an essential one in the future learning perspective. Findings conclude that the experiential learning foster student’s abilities in solving the problem and thereby gaining confidence during e-learning and placement activities and the grading process are to be updated through centralized servers to the maximum extend and accuracy are to be maintained.